2023
DOI: 10.5455/javar.2023.j665
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine reduces severity and mortality in COVID-19 patients: A systematic review and meta-analysis

Mohammad Alam,
Mohammad Hasan,
Zannatul Maowa
et al.

Abstract: Objectives: Recent clinical studies suggest that oxidative stress is one of the key players in the pathogenesis of coronavirus disease 2019 (COVID-19), and N-acetylcysteine (NAC), a potent anti¬oxidant, has been shown to improve clinical outcomes in COVID-19 patients. We conducted a systematic review and meta-analysis of the literature published on the therapeutic intervention of NAC on COVID-19 infection. Methods: We searched PubMed, Google Scholar, and Science Direct. We identified and screened eight studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…78 In a meta-analysis of mixed studies, NAC was shown to reduce mortality (RR = 0.65 [0.56-0.75]). 79 COVID-19 mortality data in SGLT2i users is inconclusive, with a RCT and a meta-analysis both reporting no significant results while another metaanalysis reported pre-admission use to be associated with decreased mortality in diabetics (OR 0.69 [0.56 -0.87]). 76,80,81 No significant results were reported in studies of bisphosphonates, MB, ACEi/ARB, or aspirin; however, the meta-analysis of RCTs and aspirin only investigated anti-platelet level dosing, not anti-inflammatory.…”
Section: Covid-19 Mortalitymentioning
confidence: 99%
“…78 In a meta-analysis of mixed studies, NAC was shown to reduce mortality (RR = 0.65 [0.56-0.75]). 79 COVID-19 mortality data in SGLT2i users is inconclusive, with a RCT and a meta-analysis both reporting no significant results while another metaanalysis reported pre-admission use to be associated with decreased mortality in diabetics (OR 0.69 [0.56 -0.87]). 76,80,81 No significant results were reported in studies of bisphosphonates, MB, ACEi/ARB, or aspirin; however, the meta-analysis of RCTs and aspirin only investigated anti-platelet level dosing, not anti-inflammatory.…”
Section: Covid-19 Mortalitymentioning
confidence: 99%
“…As the levels of GSH decline with age [ 45 ], positive effects of supplementation with NAC in combination with glycine on changes associated with aging have been successfully tested in clinical trials [ 46 , 47 ]. Because GSH concentrations also decrease in various disorders with abundant oxidative stress [ 48 ], NAC has been used in a variety of respiratory diseases, including COPD [ 49 ], IPF [ 19 ], lung silicosis [ 50 ], COVID-19 [ 51 , 52 ], or obstructive sleep apnea [ 53 ], as well as in multidrug-resistant infections [ 54 ], cardiovascular diseases [ 55 ], type 2 diabetes [ 56 ], chronic nephropathy [ 57 ], or infertility due to polycystic ovaria [ 58 ].…”
Section: Pharmacological Effects Of Nacmentioning
confidence: 99%